2022
DOI: 10.1088/1612-202x/ac4be7
|View full text |Cite
|
Sign up to set email alerts
|

All fiber structured supercontinuum source based on graded-index multimode fiber

Abstract: We provide an all fiber spectrally flat supercontinuum (SC) source generated by pumping a 20 m graded-index multimode fiber (MMF). The fiber pigtails of the all-fiber pump pulse laser and the MMF fused with a special method. After measuring the spectrum and the power, the output power extending from the visible to the mid-infrared is 2 W. To the best of our knowledge, this is the first watt-class and spectrally flat all fiber structured SC source based on graded-index MMF. Finally, we studied the evolution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…reported that a supercontinuum with an output power of 3.96 W was achieved in a GRIN MMF with 62.5 µm core diameter using picosecond pulses at MHz repetition rate [13]. There are also some reports on the generation of supercontinuum in GRIN fibers [14,15]. However, current studies on the generation of supercontinuum spectra based on GRIN fibers were all performed at lower average powers (below 5 W).…”
Section: Experiments Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that a supercontinuum with an output power of 3.96 W was achieved in a GRIN MMF with 62.5 µm core diameter using picosecond pulses at MHz repetition rate [13]. There are also some reports on the generation of supercontinuum in GRIN fibers [14,15]. However, current studies on the generation of supercontinuum spectra based on GRIN fibers were all performed at lower average powers (below 5 W).…”
Section: Experiments Setupmentioning
confidence: 99%
“…There are also some reports on the generation of supercontinuum in GRIN fibers [14,15]. However, current studies on the generation of supercontinuum spectra based on GRIN fibers were all performed at lower average powers (below 5 W).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the effective shortwave extension of the SC driven by the GPI effect in the GRIN MMF requires a high pump peak power. Based on this reason, the maximum average output power of the SC generation from the GRIN MMF with an all-fiber structure is only maintained at about 2 W, as reported in 2022, and the corresponding spectrum covers the wavelength from 450 nm to beyond 2400 nm [17] .…”
Section: Introductionmentioning
confidence: 97%
“…Supercontinuum sources have a wide range of applications in metrology [14], biomedicine [15], national defense and security [16], and environmental monitoring [17]. The richer nonlinear effects in MMFs benefit the generation of supercontinuum, so the study of supercontinuum in MMFs has attracted widespread interest [18][19][20][21]. Depending on the dispersion characteristics of the medium and the parameters of the pump source, the dominant nonlinear effects in the SCG will also be different.…”
Section: Introductionmentioning
confidence: 99%